Marketing and managing tourism destinations - Morrison, Alastair M., ....- (Oxon : Routledge, 2023)
Marketing and Managing Tourism Destinations is a comprehensive and integrated introductory textbook covering destination management and marketing in one volume. It focuses on how destination management is planned, implemented, and evaluated as well as the management and operations of destination management organizations (DMOs), how they conduct business, major opportunities, and challenges and issues they face to compete for the global leisure and business travel markets. Much has changed since the publication of the second edition of this book in 2018. The COVID-19 pandemic was unpredictable at the time and has caused havoc for destinations and DMOs. The third edition includes many materials about the COVID-19 impacts and recovery from the pandemic.
Keywords: Toerisme ; management; Toerisme ; marketing